Transformasi Nilai-Nilai Moral Islami dalam Novel Karya Ramadhan K.H. sebagai Dakwah Kultural: The Transformation of Islamic Moral Values in Ramadhan K.H.'s Novels as Cultural Preaching - Abd. Rahman Ds (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2010)
Within the latest information media, the process of cultural contact occurs rapidly. While it has positive effects, it also brings negative impacts, including the fading of societal concern for Islamic moral values. To mitigate these negative effects, cultural preaching through the reading of Islamic novels titled The Transformation of Islamic Moral Values in Ramadhan K.H.'s Novels as Cultural Preaching is necessary. This research employs a moral approach, using descriptive-interpretative analysis techniques, and finds that Ramadhan K.H.'s novels are rich in Islamic moral values such as gratitude, patience, trustworthiness, consistency, and resignation to God's will. Dalam media informasi mutakhir, proses kontak budaya berjalan dengan cepat. Selain memberikan dampak positif, hal ini juga menimbulkan dampak negatif, termasuk memudarnya kepedulian masyarakat terhadap nilai-nilai moral Islami. Untuk menghindari dampak negatif tersebut, diperlukan dakwah kultural melalui pembacaan novel Islami berjudul Transformasi Nilai-Nilai Moral Islami dalam Novel Karya Ramadhan K.H. sebagai Dakwah Kultural. Penelitian ini dilakukan dengan pendekatan moral, menggunakan teknik analisis deskriptif-interpretatif, dan menemukan bahwa novel Ramadhan K.H. sarat dengan nilai-nilai moral Islami seperti syukur, sabar, amanah, istiqomah, dan tawakal.